Control of Herpesvirus Infection in Organ Transplant Recipients - Nina E Tolkoff-Rubin; Robert H Rubin (Canadian Journal of Infectious Diseases)
The most important causes of infectious disease morbidity and mortality in organ transplant recipients are the herpesviruses, particularly cytomegalovirus (CMV) and Epstein-Barrvirus (EBV). Because of their properties of latency, cell association, and potential oncogenicity, they are particularly well suited to causing disease in the transplant patient. Antilymphocyte antibody therapies are potent reactivators of these viruses, and cyclosporine, by inhibiting the critical host defense (virus specific cytotoxic T cells) in a dose-dependent fashion, amplifies the extent and effects of the viral replication. This in turn is translated into clinical disease: fever; pneumonia; gastrointestinal ulcerations; broad-based suppression of host defences leading to opportunistic superinfection and, perhaps, allograft injury in the case of CMV; and B cell lymphoproliferative disease in the case of EBV. New approaches to controlling these viruses in which pre-emptive therapy is linked to immunosuppressive therapy, and new diagnostic techniques for viral monitoring, hold promise for limiting clinical disease due to these viruses.